Process Approach in Results-oriented Public Administration - NURHALIEVA, Dulpariz; OMIRBAEV, Serik; TUREBEKOVA, Bazhan; BOPIYEVA, Zhamila (Journal of Advanced Research in Law and Economics, 2017)
Kazakhstan is currently used functional approach in public administration. However, in carrying out their functions, employees don’t see the end results of the state body work in the whole and be aware of their place in the overall chain of activities. Consequently, the functional system directs workers to perform functional duties well, but do not orient them to achieve results. However, in terms of results-based budgeting, application of the functional approach does not meet the requirements of the new system of government. Therefore, there is a question about the choice of a different approach in the management, which would be oriented public authorities to achieve the result. In addressing remedial shortcomings of functional approach in the management the foreign experience is visual. In world practice for a long time and successfully applied the process approach. However, this issue did not find an adequate reflection in the research of Kazakhstani scientists. Therefore, this issue has become a subject of study in this article as it is relevant to the realities of a modern public sector management of Kazakhstan's economy.